(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article discusses the issue of place names being translated from English into Uzbek and their translation. In the translation process, it is important to accurately and precisely express place names, take into account cultural, historical and geographical contexts. The article examines the main difficulties that arise in the translation of place names, the methods by which translators translate such names, and what they should pay attention to in this process. The theory and practice of translation analyzes the changes in place names, the differences between English and Uzbek place names, as well as the importance of place names in globalization processes. It also discusses errors that occur when translating place names and ways to correct them.